A critique of the urban community life and institutional networks of urban ratepayers in Masvingo, Zimbabwe - Mhandu, John; Batisai, Kezia (Faculty of Social and Political Science, Universitas Airlangga, 2024)
This article explores the coping strategies employed by urban ratepayers to withstand their prolonged infrastructure problems. The main argument herein is that urban ratepayers make use of different individual and collective coping and resilience strategies to endure infrastructure problems. The article provides a critique of urban community life and institutional networks or urban ratepayers in Masvingo, Zimbabwe, in the wake of fragmenting urban infrastructure during 2015-2019. The study utilised qualitative methods grounded on the interpretivist research paradigm. A total of 17 in-depth interviews and documentary reviews were conducted. The article establishes that constant engagement with key institutions, namely Masvingo Business Advisory Board (MBAB), Masvingo United Residents and Ratepayers Association (MURRA), Community-Based Organisations (CBOs) and civil society initiatives represents a fundamental and ongoing strategy for the urban ratepayers in Masvingo. In explaining the broad range of practices adopted by elite urban ratepayers, the article views coping strategies in urban Masvingo as a pursuit of the autonomous interest of individuals or a class/group (whether business people or residents in a particular area). Although these are autonomous pursuits based on class interest, the article argues that some of the coping strategies adopted at the institutional level do not harm but benefit society at large.